Redox‐Flow‐Batteries: Aqueous Redox Flow Battery Suitable for High Temperature Applications Based on a Tailor‐Made Ferrocene Copolymer (Adv. Energy Mater. 41/2020). Issue 41 (3rd November 2020) - Borchers, Philipp S.; Strumpf, Maria; Friebe, Christian; Nischang, Ivo; Hager, Martin D.; Elbert, Johannes; Schubert, Ulrich S.
Abstract : In article number 2001825 Ulrich S. Schubert and co‐workers present the first high‐temperature stable polymer for Redox‐Flow‐Batteries (RFB), enabling applications in connection with solar and wind parks in warm environments without cooling the battery (up to 60 °C). This will significantly contribute to a future energy transition with a reduced CO2 footprint.